Paleogenetic and morphometric analysis of a Mesolithic individual from Grotta d'Oriente: An oldest genetic legacy for the first modern humans in Sicily. (15th November 2020) - Modi, Alessandra; Catalano, Giulio; D'Amore, Giuseppe; Di Marco, Sylvia; Lari, Martina; Sineo, Luca; Caramelli, David
Abstract: Grotta d'Oriente, a coastal cave located on the island of Favignana (Sicily, Italy) is a key site for the study of the early human colonization of Sicily. Inside the cave, during different field excavations, three burials attributable to the Late Upper Palaeolithic and Mesolithic were found. The Mesolithic Oriente B individual, directly dated at 9, 377 ± 25 uncal BP, was previously assigned to HV1 haplogroup using a traditional approach. However, it is well known that PCR based methods are prone to erroneous haplotype or haplogroup determination. In order to redefine the mitochondrial lineage of this Mesolithic hunter-gatherer and explore its phylogenetic position, we target-enriched and sequenced the complete mitochondrial genome of Oriente B. Moreover, we conducted a morphometric analysis to assess its phenetic affinities. Oriente B individual was classified into U2′3′4′7′8′9 haplogroup. In Sicily, this lineage has also been found on the Upper Palaeolithic Oriente C and Early Mesolithic individuals from Grotta dell'Uzzo. Our results show significant genetic and morphological similarities in Sicilian Early Mesolithic hunter-gatherers, presumably because of genetic drift processes. Furthermore, dating the emergence of the "Sicilian clade", we speculate that Epigravettian hunter-gatherers carrying U2′3′4′7′8′9 haplogroup might be the first settlers of Sicily arrived from the Italian peninsula by the crossing of a temporary land-bridge around the Last Glacial Maximum. Highlights: New ancient DNA data obtained from Mesolithic Oriente B. Reveals genetic and morphological similarities among Sicilian Mesolithics. U2′3′4′7′8′9 haplogroup linked to the early colonization of Sicily by modern humans. A "Sicilian clade" mtDNA diverged from the European mainland 23, 248 years BP. Humans exploited a land-bridge connecting Sicily to Italian peninsula during LGM.